Analisis Hibah dalam Pemberdayaan Masyarakat dan Pertumbuhan Ekonomi: Studi Literatur dan Implementasi Kebijakan - Hafidha Anirotush Sofia; Tiara Azzahra; Siti Hawa Laili Yuliana; Faizatul Muniroh; , Hilmi Shidqi Finanda; Muhammad Ikmal Fahmi; , Ajmal Wulida M; Riko Jonathan H (Pusat Riset dan Inovasi Nasional, 2025)
Grants are a form of financial assistance provided by individuals, organizations, or governments to recipients without repayment obligations. Grants play a significant role in social and economic development, including improving community welfare, strengthening economic capacity, and supporting infrastructure development. This study aims to analyze how grants contribute to community empowerment and economic growth while identifying challenges in their management. Using a qualitative approach based on a literature review, this study finds that well-managed grants can enhance the competitiveness of small and medium enterprises (SMEs), accelerate regional development, and support social sectors such as education and health. However, issues such as lack of transparency, weak supervision, and potential dependency among grant recipients remain significant challenges. Strengthening regulations, implementing monitoring systems, and ensuring impact-based grant distribution are recommended to improve grant effectiveness and maximize benefits for recipients.